أثر الاصلاحات النقدية على الصلابة المصرفية دراسة مقارنة بين الجزائر و موريتانيا ( 2016-2019) - رمضاني, محمد; ولد حام ولد حكي, الطالب مصطفى (جامعة الوادي - University of Eloued, 2021)
يهدف هذا المقال إلى إعادة تقييم الاصلاحات النقدية التي قامت بها الدول النامية ، خاصة الجزائر و موريتانيا . و التي كانت معظم ملامحها نتيجة توصيات صندوق النقد الدولي في سنوات التسعينيات، و كيف أثرت بعد سنوات على أداء و تطور و صلابة أهم قطاع اقتصادي يهتم بتمويل الاقتصاد و هو القطاع المصرفي في البلدين . تنتهج هذه الدراسة مقاربة تحليلية، تقييمية و مقارنة ، وفقا للمنهجين التحليلي و المقارن. كما مثلت حدود الدراسة الزمنية خمس سنوات من 2016 الى 2019 . و هي السنوات الأصعب من الناحية المالية بعد تراجع ايرادات الدول نتيجة انخفاض أسعار البترول والمعادن في الاسواق العالمية. توصلت هذه الدراسة الى أن الاجهزة المصرفية الجزائرية و الموريتانية عرفت نوعا من العمق المالي ، و تطورت خدماتها المالية ، لكن صلابتها المالية مازالت تحتاج المزيد من التعزيز. Abstract: This article aims to re-evaluate the monetary reforms undertaken by developing countries, especially Algeria and Mauritania. Most of its features were the result of the recommendations of the International Monetary Fund in the 1990s, and how it affected, after years, the performance, development and solidity of the most important economic sector concerned with financing the economy, which is the banking sector in both countries. This study follows an analytical, evaluative and comparative approach, according to the analytical and comparative approaches. The time limits of the study were five years extending from 2016 to 2019. And these are the most difficult years financially, after the decline in state revenues as a result of the decline in oil prices in the global markets. This study found that the Algerian and Mauritanian banking systems knew a kind of financial depth, and their financial services had developed, but their financial strength still needed more strengthening. Keywords: Monetary reforms; financial solidity; the Algerian banking system; the Mauritanian banking system.
مقال
Keywords: Monetary reforms; financial solidity; the Algerian banking system; the Mauritanian banking system.